Ethnic differences in patient perceptions of heart failure and treatment: the West Birmingham heart failure project. Issue 9 (13th August 2004) - Lip, G Y H; Khan, H; Bhatnagar, A; Brahmabhatt, N; Crook, P; Davies, M K
Abstract : Objective: To investigate further the hypothesis that ethnic groups would have different levels of knowledge and perceptions of congestive heart failure (CHF) and treatments for this condition, a cross sectional survey was conducted of patients who were attending the heart failure clinics in two teaching hospitals of Birmingham, UK, that serve a multiethnic population. Methods: 103 patients with CHF (66 men, 37 women) were surveyed by standard questionnaire: 42 were white, 34 Indo-Asian, 22 Afro-Caribbean, and 5 Oriental. Results: When asked about their beliefs about control of one's health, 22 (64.7%) of Indo-Asians felt that God/fate controlled their health. The majority of white patients tended to believe that the greatest factor influencing their health was the doctor (15 (35.7%)). Of the total study cohort, only 68 (66%) of patients were aware of their primary diagnosis of heart failure; the majority of Indo-Asians (21 (61.8%)) were not aware of their diagnosis. Half of Indo-Asians (17 (50%)) felt that heart failure was not severe, in contrast to 40.9% (n  =  9) of Afro-Caribbeans and only 19.1% (n  =  8) of white patients. Of the study cohort, 38 (36.9%) were taking their drugs because their doctor told them to, a response most common among the Indo-Asians. The majority of Indo-Asians (22 (64.7%)) and Afro-Caribbeans (14 (63.6%)) stated that they did not have, or did not know whether they had enough, information about their drug. The corresponding figure for white patients was 21.4% (n  =  9). When asked whether they took their medication regularly as prescribed, 7 (31.8%) of Afro-Caribbeans reported that they did not take their drugs regularly. Conclusions: Our study has highlighted deficiencies in the knowledge of CHF among patients from ethnic minority groups, as well as deficiencies in the information being given to these patients. There is a clear need to invest more in patient education for CHF, with special emphasis on certain high risk subgroups.